ANALISIS KESULITAN BELAJAR MEMBACA PADA MATA PELAJARAN BAHASA INDONESIA SISWA KELAS I SD NEGERI 33 LUBUKLINGGAU - Deka Yuliana Audiya; Akmal Rijal, Armi Yuneti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the difficulties of students in learning to read in the Indonesian Language subject of grade I students of SD Negeri 33 Lubuklinggau and to find out the solutions of students who experience difficulties in learning to read in the Indonesian Language subject of grade I students of SD Negeri 33 Lubuklinggau. The subjects of the study were grade I students of SD Negeri 33 Lubuklinggau with a total of 20 students. The type of research used is descriptive research using a qualitative approach with data collection techniques used are observation, interviews, questionnaires and reading tests. The data analysis technique used in this study is qualitative. The results of this study indicate that there are difficulties in students learning to read such as difficulties in recognizing letters, difficulties in distinguishing letters, difficulties in spelling, reading books too close to the eyes and lack of memory when reading. The solution to overcome difficulties in learning to read can be concluded as follows: By providing support such as the habit of reading after writing, paying attention and providing motivation to students, providing additional hours and free time and teachers must also provide an approach, guide and create a comfortable atmosphere, communicate with parents of students, teachers use learning media, teachers never blame students for the conditions they experience and provide special remedial reading programs.